Environment - Tewari, D. N. (Indian Forester, 1991)
Increasing population, urbanisation and industrialisation are causing pollution. The drive to produce enough food to support a growing population has resulted in the use of increasingly marginal resources, the application of harmful fertilizers and agricultural chemicals, and a full scale assault on the world’s remaining forest lands. However food security can be achieved only by developing forests which protect soils, conserve water and ameliorate microclimate. For sustainable development forestry has to be developed on priority basis since forests provide a renewable source of materials, energy and other services and belp in reducing environmental crises. Creation of healthy environment is possible only by adopting sustainable strategy for survival.